Extraction, identification and anti-inflammatory activity of carotenoids out of Сapsicum Anuum L. - Yurii Aleksandrovich Boiko; Irina Anatolievna Kravchenko; Alexey Antonovich Shandra; Irina Anatolievna Boiko (Shahrekord University of Medical Sciences, 2017)
Introduction: Carotenoids extracted from dried peppers were evaluated for their anti-inflammatory activities. Methods: Determining the concentration of carotenoids was carried out by spectrophotometry. Anti-inflammatory activity was studied on the model adjuvant-induced inflammation. In addition, the total number of white blood cells was studied by microscopic method in Gorjaev's chamber. The biochemical parameters of blood - cholinesterase activity and total number of seromucoids in blood plasma were determined by the commercial test kits for rapid analysisResults: Peppers had a substantial carotenoid content: Ukrainian bitter 2076 ± 10 μg/g of sample in dry weight basis. The yellow fraction was 69.3%, the red fraction was 30.7%. The linear decrease of inflammatory edema in the course of therapeutic use of carotenoid extract ranged from 20% to 50%. The application of carotenoid extract reduced levels of activity acetylcholinesterase and concentration of seromucoids in serum of rats with adjuvant-induced inflammation. The use of carotenoid extract in rats with adjuvant-induced inflammation resulted in reduction of serum cholinesterase activity by 1.3 times and double decrease in the serum seromucoid concentration. Conclusion: Ukrainian bitter pepper carotenoid extract exhibited good anti-inflammatory activity, with inhibited adjuvant-induced oedema formation and progression. The results suggest that the carotenoids in dried Ukrainian bitter peppers have significant anti-inflammatory benefits and could be useful for pain and inflammation relief. The results of this study allow to recommend carotenoid extract for further investigation as active part of anti-inflammatory drugs.